(untitled) (Baghdad Science Journal, 2021)
High-intensity laser-produced plasma has been extensively investigated in many studies. In this demonstration, a new spectral range was observed in the resulted spectra from the laser-plasma interaction, which opens up new discussions for new light source generation. Moreover, the characterizations of plasma have been improved through the interaction process of laser-plasma. Three types of laser were incorporated in the measurements, continuous-wave CW He-Ne laser, CW diode green laser, pulse Nd: YAG laser. As the plasma system, DC glow discharge plasma under the vacuum chamber was considered in this research. The plasma spectral peaks were evaluated, where they refer to Nitrogen gas. The results indicated that the plasma intensity increased from several thousands to several tens of thousands through the process of interaction of the Nd: YAG laser with the plasma. This increase in the intensity of the plasma as laser intensity increased occurs regardless of laser wavelength involved in the interaction or not. According to laser-plasma interaction, the so-called full width at half maximum FWHM of the highest peak in the plasma spectrum was broadened from 1.43 to 2.73. Considering the equation of plasma density computing, the plasma density was increased from 1.07× 1018 to 2.05× 1018 cm-3 with increasing FWHM. As a result of the interaction, the electron temperature of plasma was increased from 0.176 to 0.782 eV. It was also noticed that the position of the highest peak in the plasma spectrum depends on the interacted laser wavelength.